Factors determining the Level of Customer Trust in Online Travel Shopping - Manocha, Annum (2008)
The purpose of this study was to determine the dimensions of customer trust in the context of Internet travel shopping. Based on the related literature on relationship marketing in online as well as offline contexts, the study proposed four main factors affecting customer trust towards Internet-based travel Websites. These are perceived quality of travel Web services, institution-based trust, calculative-based trust and trusting beliefs of the online vendor. The study began by testing the developed survey questionnaire on small sample of customers who had a significant level of experience with Iternet-based travel Websites. The final survey questionnaire using electronic mail service generated hundred usable responses. Exploratory Factor Analysis using Principal Component Analysis was performed on thirteen trust measures of customer trust in online travel shopping. These variables were grouped into two factors. The factors were denoted as perceived quality in travel Web services and perceived trustworthiness of online travel agencies. Independent sample t-tests run on the trust measurement constructs in online travel shopping indicated no significant difference for males and females. Thereafter, multiple regresson analytical technique was utilised to determine the relative contribution of the two factors in the prediction of customer trust in online travel shopping. In this regard, it was found that perceived trustworthiness of online travel agencies had a higher predictive value in the formation of customer trust. This study is important as few online travel businesses have developed Internet-based travel Websites that is based on establishing a significant level of relationship with the customer. More importantly, there exists a lack of research to guide the online travel agencies in understanding online customer trust. In this regard, this study established that increasing the perceptions of trustworthiness in the travel Websites as well as the travel service quality will aid online travel businesses in achieving a successful relational exchange.